The legal protection of sea turtles: a comparative study between Terengganu and Perak / Mohamad Firdaus Baharudin, Nur Diana Ramlan and Zarith Satina Md Sani - Baharudin, Mohamad Firdaus; Ramlan, Nur Diana; Md Sani, Zarith Satina (2011)
Sea turtles inhabit the world's entire oceans except the Arctic. Notwithstanding that they can be found almost everywhere, they are actually small in population. Moreover, the sea turtles are threatened by both human and inhuman predators as well as the changes in the ecosystem. The absence of specific laws in our country that accord protection to sea turtles makes it even more difficult to provide protection to sea turtles. This research aims to analyze the law that provides protection to sea turtles in the states of Terengganu and Perak, to highlight the differences of the law applied between the two states, as well as to suggest legal ways to remedy the problems involved. The method adopts in this research is of qualitative type. Thus, it incorporates library and internet based research as well as semi-structured interviews. From the research, the result shows that protections of sea turtles by the two states are indeed differ. The State of Terengganu provides wider scope of protection than Perak. The idea to standardize the legislation throughout Malaysia is shown to be impractical. Thus alternatively each state has to enhance their legislation to accord better protection to sea turtles.